The impact of the digital economy on the servitization of industrial structures: the moderating effect of human capital - Ran, Rong; Wang, Xinyuan; Wang, Ting; Hua, Lei (Data science and management, 2023)
The digital economy, which was born during the late third technological revolution, has caused significant economic and societal changes. Amid sluggish global economic growth, China’s economy is facing upgrades and transformations. The sample selection for this study was conducted from 2013 to 2020. Data related to the digital economy and servitization of the industrial structure of 30 Chinese provinces, municipalities, and autonomous regions were collected. This study presents the human capital variable, based on which an econometric analysis was conducted, and examines its moderating effect. The findings indicate that even after the replacement variable indicator’s robustness test, the relationship between the digital economy and the servitization of industrial structures remains unchanged. This study demonstrats that the quality of human capital plays a positive role in this effect. Finally, a heterogeneity test demonstrated that there are different pathways for the impact of the digital economy on the servitization of industrial structures in the eastern, central, and western regions. This study provides evidence to help researchers understand the moderating utility of human capital.